Solve the equation
5(- 3x - 2) - (x - 3) = -4(4x + 5) + 13
Answers
Answered by
1
Given the equation
5 (- 3 x - 2) - (x - 3) = - 4 (4 x + 5) + 13
Multiply factors.
-15 x - 10 - x + 3 = - 16 x - 20 + 13
Group like terms.
- 16 x - 7 = - 16 x - 7
Add 16x + 7 to both sides and write the equation as follows
0 = 0
The above statement is true for all values of x and therefore all real numbers are solutions to the given equation.
Answered by
0
y=-x-13
4x-3y=-17
----------------
Substitute for "y" and solve for "x":
4x - 3(-x-13) = -17
---
4x + 3x + 39 = -17
7x = -56
x = -8
------------------
Since y = -x-13, y = 8-13 = -5
---
Solution: (-8,-5)
----
#BE BRAINLY
Similar questions